A natural element updated Lagrangian approach for modelling fluid structure interactions - Galavís, Andrés; González, David; Cueto, Elias; Chinesta, Francisco; Doblaré, Manuel (European Journal of Computational Mechanics, 2007)
In this paper we present a novel methodology for the numerical simulation of fluid structure interactions in the presence of free surfaces. It is based on the use of the Natural Element Method (NEM) in an updated Lagrangian framework, together with the integration of the Navier-Stokes equations by employing a Galerkin-characteristics formulation. Tracking of the free-surface is made by employing shape constructors, in particular α- shapes. A theoretical description of the method is made and also some examples of the performance of the technique are included.